Analysis of Patterns for Inheritance Dispute Settlement in the Tradition of Sasak Community in Lombok - haji munir, zainal arifin (Mazahib, 2021)
There are several ways conducted by Muslims in solving the problem of inheritance division in Lombok. This article aimed at looking at several patterns of inheritance dispute resolution in the Lombok people tradition (Sasak community. It is derived from qualitative field research by using both theoretical and empirical legal approaches. The data was obtained using observation, interview, and documentation techniques. Lombok people often postpone dividing the inheritance, which eventually causes problems. According to Lombok customary law, postponing inheritance is carried out due to several cultural factors, i.e.: the existence of the parent (either father or mother), the existence of the heirs, and the condition of the heirs. Apart from these factors, several consequences arise including loss of ownership rights, changes in inheritance portion, loss of inheritance rights, vulnerability to manipulation, and triggering family conflicts. The results indicate that: first, the inheritance land division is conducted in different ways such as grants, discussion, and faraid. Second, factors influencing the land dispute cases are greed and lack of information about the inheritance legal system. Third, revitalization is important because it is ruled out in Islamic teachings and is considered absolute for Islam society. This research concludes that the Islamic Inheritance legal system is the proper method to settle land disputes in the Sasak community. Keywords: Islamic inheritance, postponing inheritance, settlement of inheritance disputes.